Hook effect and serum KL-6 in Patients with Systemic Sclerosis-Associated Interstitial Lung Disease (SSc-ILD) (International Journal of Integrated Health Sciences, 2021)
Objective To determine whether serum KL-6 can be used as an alternative diagnostic tool for Systemic Sclerosis-associated ILD (SSc-ILD).Method This was a cross-sectional study with compatibility analysis of SSc patients visiting the rheumatology clinic of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia in 2019-2020. Inclusion criteria were aged 18-60 years, diagnosed with SSc, restrictive spirometry results followed by HRCT thorax, having stored biological materials (
Keywords: hook effect; ILD; KL-6; systemic sclerosis